2017
DOI: 10.1093/eurheartj/ehx687
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality in patients with atrial septal defect: a nationwide cohort-study

Abstract: AimsIn this nationwide cohort of atrial septal defect (ASD) patients, the largest to date, we report the longest follow-up time with and without closure in childhood and adulthood compared with a general population cohort.Methods and resultsUsing population-based registries, we included Danish individuals born before 1994 who received an ASD diagnosis between 1959 and 2013. All diagnoses were subsequently validated (n = 2277). Using the Kaplan–Meier estimates and Cox proportional hazards regression adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 25 publications
6
70
1
Order By: Relevance
“…We submit, however, that the excellent outcome reported herewith largely reflects our proactive approach of offering ASD closure mainly for prognostic reasons before cardiac decompensation and overt symptoms ensue. This contrasts to historical studies of pioneering era of cardiac surgery7 and reports of registries span over a long period of intervention with a different and more ‘reactive’ approach and also longer periods of follow-up, both relevant to the different outcomes reported in these studies, compared with the present study 15. We have clearly come a long way in ASD closure.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We submit, however, that the excellent outcome reported herewith largely reflects our proactive approach of offering ASD closure mainly for prognostic reasons before cardiac decompensation and overt symptoms ensue. This contrasts to historical studies of pioneering era of cardiac surgery7 and reports of registries span over a long period of intervention with a different and more ‘reactive’ approach and also longer periods of follow-up, both relevant to the different outcomes reported in these studies, compared with the present study 15. We have clearly come a long way in ASD closure.…”
Section: Discussioncontrasting
confidence: 90%
“…While overall reduction in morbidity and consequently improvement in quality of life has been shown after closure of ASD irrespective of age,19–21 life expectancy of patients with ASD closure in adulthood is nevertheless considered to be impaired when compared with healthy controls 15. Our contemporary data show that a proactive ASD closure approach in adulthood is associated with normal survival compared with that expected in the general population matched for gender and age in the mid to longer term follow-up.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with small, unrepaired ASD were once believed to be as healthy as the general population; however, this notion has been called into question. We have demonstrated that patients with a small, unrepaired ASD that persists into adult life have increased risk of premature death (mean age of death was 63 years), more chronic diseases, worse functional capacity, higher levels of stress, and lower scores on self‐assessed physical function compared to the general population …”
Section: Introductionmentioning
confidence: 99%
“…8 Evidence clearly suggested that untreated large secundum defects are associated with a reduced lifespan. 8 Evidence clearly suggested that untreated large secundum defects are associated with a reduced lifespan.…”
Section: Discussionmentioning
confidence: 99%